PENGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 015 PENYAGUAN KECAMATAN BATANG GANSAL - Mahli '; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : this research is motivated by the fact that is found in the class V SDN 015 Penyaguan, whict shows the results of learning in IPS is still relatively low, formulation the problem is this research is: “does the application kooperatif tife make a match model can improve learning outcomes in IPS students of SDN 015 Penyaguan Kecamatan Batang Gansal Kabupaten Indragiri Hulu ?“. this research aims to improve learning models make a match, the hypothesis og this study is that if applied learninr model kooperatif tife make a match it can improve learning outcomes in aprl students of SDN 015 Penyaguan .this study was conducted in eas much as two cycle. The subjects were students of class sdn 015 Penyaguan 2016. This from is research is classroom action researth(PTK)are planned as IPS as two cycle. The subjecth were students of class V SDN 015 Penyaguan. which amounted to 34 peopel consisting of 16 men and 18 women. Based on the results of research of teacher activity sheet senn rising eachmeeting. At the first meeting of the first cycle of 62,63%, the second meeting of the firstcycle of I 71,88%, at the fourth meeting of the cycle of 78,13%, the second metting of the first cycle of 87,5%. At the fourth meeting of the second cycle of 56,52%, at the meetingof the second cycle 8,75%, at the fourth meeting of the secontcycle of 71,88%, and the fifth meeting of the second cycle of 81,25%. Mastery learning outcomes to repeat at first cycle increased 2,47% from the base score of 65,29% the average value in the base score 62,82%, UH then average value of UH II becomes 80,65% with an increase 19.09%. so that research result are consistent with the hypothesis.Key Word: kooperatif tife make a match model, learning autcomes IPS